DEVELOPMENT OF BIG DATA INFORMATION TOWARD QUALITY EDUCATION - Husna, Fatimatul; Baharun, Hasan; Andayani, Sri Astutik (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The era of Industrial Revolution 4.0 stimulates the application of big data in various sectors, including education, to support better decision-making and improve service quality. At the Vocational High School (SMK) level, big data has great potential to help schools adapt to changing industry needs, especially regarding graduates who are competent in technology and information. This research aims to examine the implementation and development of big data information systems at Nurul Jadid Vocational School to improve the quality of education. This research uses a qualitative case study approach, collecting data through observation, interviews, and documentation. The research results show that applying big data at Nurul Jadid Vocational School supports improving the quality of education by making it easier to manage student and teacher data, monitor learning achievements, and develop student competencies. This research produces findings: a). Digitalization and Management of Academic Data at Nurul Jadid Vocational School b) Collaboration with other industries c). Nurul Jadid Vocational School Digital Library. It is hoped that this research will become a reference for other vocational education institutions that wish to utilize big data technology to improve the quality of education.